Investigation of the Techno-Economical Feasibility of the Power-to-Methane Process Based on Molten Carbonate Electrolyzer - Monzer, Dayan; Rivera-Tinoco, Rodrigo; Bouallou, Chakib (Frontiers in Energy Research, 2021)
High-temperature Steam/CO2electrolysis process is under the scope of study in the last decades. It confers a feasible and environmental approach to convert low-carbon electrical energy into chemical energy stored in the form of synthetic gas (H2 & CO) to be further processed in line with the final use target. This work focuses on the Power to Methane technology using high-temperature Molten Carbonates electrolyzers (MCEC). Throughout this mission, a large-scale process composed of the build-in MCEC model and the Balance of Plant BOP equipment is proposed and simulated in AspenPLUS software, taking into consideration the possible heat integration in the system for saving energy consumption. The proposed full-based process system shows an overall efficiency of 65%. The employment of this carbon-neutral process relies on its economic competitiveness. For this reason, an economic assessment is conducted to investigate the economic feasibility of the proposed process. Indeed, current methane production cost resulting from this process is not as competitive relative to market prices induced by other technologies. However, a parametric study demonstrating the impact factors on the methane selling price reveals that the amelioration in the electrolyzer’s lifespan accompanied by a reduction in its cost can be an attractive solution given the current market technology. This overall analysis sheds light on the role of the proposed process as an environmental-friendly and cost feasible solution for synthetic methane production.